Reimagining cost recovery in Pakistan’s irrigation system through willingness-to-pay estimates for irrigation water from a discrete choice experiment - Bell, A.R.; Ali Shah, Azeem M.; Ward, Patrick S. (Wiley, 2014)
It is widely argued that farmers are unwilling to pay adequate fees for surface water irrigation to recover the costs associated with maintenance and improvement of delivery systems. In this paper, we use a discrete choice experiment to study farmer preferences for irrigation characteristics along two branch canals in Punjab Province in eastern Pakistan. We find that farmers are generally willing to pay well in excess of current surface water irrigation costs for increased surface water reliability and that the amount that farmers are willing to pay is an increasing function of their existing surface water supply as well as location along the main canal branch. This explicit translation of implicit willingness-to-pay (WTP) for water (via expenditure on groundwater pumping) to WTP for reliable surface water demonstrates the potential for greatly enhanced cost recovery in the Indus Basin Irrigation System via appropriate setting of water user fees, driven by the higher WTP of those currently receiving reliable supplies.